Emissivity Comparison between Chars and Demineralized Coal Chars under Oxycombustion Conditions. Issue 7 (11th June 2018) - Graeser, Philipp; Wütscher, Annika; Cerciello, Francesca; Muhler, Martin; Schiemann, Martin
Abstract: Char emissivity of burning particles is an important factor for heat transfer calculations in pulverized fuel boilers. As the chemical composition is known to influence the emissivity in general, a coal sample has been prepared by a leaching method to reduce the mineral content. A flat flame burner was used for the combustion of the particles in oxyfuel atmosphere, providing boundary conditions comparable to pulverized coal applications. The burnout‐dependent emissivity of the sample was measured in a defined spectral range and compared with data for an unleached sample of the same coal, indicating that the mineral content has minor effect for the investigated conversion levels, although clear changes in the emissivity show that conversion in general is not negligible. Abstract : Char emissivity of burning particles is a key factor for heat transfer calculations in pulverized fuel boilers. Char particle emissivity is determined by simultaneous optical measurements of particle size, temperature, and thermal radiation during burnout. The particles were burned under realistic conditions. The influence of the minerals is evaluated by a demineralized bituminous coal char sample.